Organizacja i świadczenie usług komunikacji miejskiej w samorządzie gminnym na przykładzie miasta Zgierza - Wasiak, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The development of public transport is aimed at providing assistance for those citizens who do not own a car and improving public transportation services so that they become more competitive and capable of standing up against individual transport. Public transport is an attempt at providing an alterative for the private car in zones with limited traffic. With the dramatic increase in use of the private car it is necessary to oppose this trend and to promote public transport in order to increase its overall share in transportation and travel. Public transport encourages structural stability in the use of space and development of commerce and transportation.Each city, including Zgierz should have its own plans of public transport development based on sound financial analysis. Public transport policy should provide guidance for breaching development barriers, especially those relating to the financial and technical aspects of the problem and facilitate the decision-making process concerning the use and development of public transport. The primary goal of public transport policy is to oppose unfavourable trends in urban communication, in particular, dominating position of the private car in residential areas. To achieve this goal it is necessary to use organisational, financial and legal resources and employ efficient planning techniques. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 723-733